PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTU MEDIA GAMBAR TERHADAP HASIL BELAJAR, KINERJA GURU, DAN AKTIVITAS SISWA ILMU PENGETAHUAN SOSIAL KELAS IV SD - Singgih Adhi P, Lynda Puspita Sari (Universitas PGRI Semarang, 2015)
This research is motivated by low yields and social studies teachers do not use a model of learning in learning. The problem in this research is